1989
DOI: 10.1093/carcin/10.1.145
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of chlorophyll on the genotoxicity of 3-amino-1-methyl-5H-pyrido[4,3-b indole (Trp-P-2)

Abstract: Genotoxicity of 3-amino-1-methyl-5H-pyrido[4,3-b]indole (Trp-P-2) on Drosophila was suppressed by chlorophyll. Using the wing hair spot test, we found that the formation of mutant hairs in adult flies as a result of feeding them with Trp-P-2 in their larval stage was efficiently inhibited by coadministration of chlorophyll. The decrease in the spot frequencies was dependent on the dose of chlorophyll, and at the highest dose used, where the ratio in weight of Trp-P-2 to chlorophyll was 1:80, a complete prevent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 116 publications
(32 citation statements)
references
References 0 publications
2
30
0
Order By: Relevance
“…The first detailed investigation of CHL-drug and related systems was performed with respect to various mutagen molecules [39,44,[198][199][200][201][202][203][204], and more recent studies [41,156,157,205,206] have extended the set of drugs to antitumor antibiotics and some other types of mutagens. It was found that chlorophylls are able to form face-toface complexes with planar molecules, and the addition of methyl groups above or below the plane of the mutagen molecule interferes sterically with overlapping CHL/ mutagen ring systems, thus reflecting the importance of 'structural complementarity' in hetero-association [156].…”
Section: International Reviews In Physical Chemistry 27mentioning
confidence: 99%
“…The first detailed investigation of CHL-drug and related systems was performed with respect to various mutagen molecules [39,44,[198][199][200][201][202][203][204], and more recent studies [41,156,157,205,206] have extended the set of drugs to antitumor antibiotics and some other types of mutagens. It was found that chlorophylls are able to form face-toface complexes with planar molecules, and the addition of methyl groups above or below the plane of the mutagen molecule interferes sterically with overlapping CHL/ mutagen ring systems, thus reflecting the importance of 'structural complementarity' in hetero-association [156].…”
Section: International Reviews In Physical Chemistry 27mentioning
confidence: 99%
“…On the other hand, CHL was demonstrated to protect against mutagenic activity of direct-acting N-hydroxy HCAs derivatives: Trp-P-2[NHOH] [44], N-OH-IQ [45], and other direct-acting aromatic compounds: benzo[a]pyrene-7,8-diol-9,10-epoxide (BPDE) [46] and aflatoxin B 1 -8,9-epoxide [47]. In contrary, no inhibitory effect of CHL was observed against small, nonplanar alkylating agents, N -methyl-Nnitrosourea (MNU) and ethyl methanesulfonate (EMS) [46].…”
Section: Interception and Other Mechanisms Of Chl Actionmentioning
confidence: 99%
“…However, in contrast to CHL, which is highly water soluble, lipophilic natural chlorophylls complex less effectively with carcinogens under the aqueous conditions of many in vitro assays. A mixture of chlorophylls a and b was shown to exhibit antimutagenic activity in the Salmonella assay by a mechanism involving complex formation [19], and purified chlorophyll a protected against the formation of DNA adducts in isolated hepatocytes by interfering with carcinogen activation [20].…”
Section: Activity Of Natural Chlorophylls In Vitro and In Vivomentioning
confidence: 99%